Investigation of Flexural Fatigue Behavior of Concrete Beams Reinforced with Intelligent CFRP-OFBG Plates - Langni Deng; Yang Liu; Ling Liao; Hong Xie; Xiaoxia Huang; Shijin Lai; Mengjun Zhong (Advances in Civil Engineering)
The fatigue properties of concrete beams reinforced with carbon fiber-reinforced polymer-optical fiber Bragg grating (CFRP-OFBG) plates under three-point bending constant cyclic loading were experimentally studied. According to the experimental findings, the mechanism of fatigue failure in reinforced beams was presented, and the corresponding empirical equations were established for the prediction of the fatigue lives of these components. Besides, based on the real-time monitoring data of the intelligent CFRP-OFBG plates, a fatigue accumulative damage model was established using flexural bending stiffness for the prediction of fatigue life. Through example verification, it was found that the fatigue life predicted by the model had less error and was safer than the fatigue failure cycle number of the reinforced beam obtained by experimental tests.